Desain dan Simulasi Kontrol Elektropneumatik Berdasarkan Displacement Step pada Alat Panen dan Tanam Wortel - Bayu Isnanta Trisna; Devanka Alfahdiya Ivandika; Farla Melvia Ramadhani; Galang Eka Dharma; Edy Setiawan (Politeknik Bosowa, 2025)
The current manual process of planting and harvesting carrots in greenhouses is considered inefficient. Therefore, automation using electropneumatic technology presents a promising solution to enhance efficiency and agricultural yield. This research aims to design an electropneumatic installation for an automatic carrot planting and harvesting tool. The method used is design and simulation control based on a displacement diagram to determine the sequence of actuator motion. From this diagram, logical equations were formulated using Boolean algebra to form the basis of the control circuit. The entire circuit was then designed and tested through simulation using Fluidsim software. The design results show that the system requires 3 cylinders groups, three 5/2-way valves, 2 proximity sensors, and 2 gripper groups operating in six sequential stages. The simulation in Fluidsim successfully proved that the designed electropneumatic circuit can function according to the predetermined logic and working sequence. Thus, this design contributes a simulation-validated automated system design with the potential to be implemented to replace the manual harvesting and transplanting of carrots